The Association Between Child Maltreatment and Family Structures: Evidence from Children in Rural China - Wan, Guowei (Journal of family violence, 2023)
Few studies have discussed the association between child maltreatment and family structure in developing countries, and this study aims to investigate this association. Data were derived from a survey of 4,180 children (Mage = 12.09, 48.44% were boys) conducted in rural China from June to December 2019. This study reaches two significant conclusions. First, the risk of child maltreatment under different family structures varied significantly. The statistical results show that the prevalence and severity of maltreatment were lowest for intact families, followed by levels for multigenerational and single-parent families, while the risk for grandparent-headed and other families was the highest. Second, the factors associated with child maltreatment differed by family structure. In intact, single-parent and multigenerational families, male caregiver variables had a strong correlation with maltreated behaviors, while female caregiver variables were highly related to maltreatment in grandparent-headed and other families. This study highlights that China’s rural children living in nonintact families are at a greater risk of experiencing child maltreatment, showing that defects in the residual child welfare system may magnify the dysfunction of fragile families.